MENTAL PREPARATIONS BEFORE THE EXAM - Ahmedjonova Dilrabo; Abdusamadova Muxlisa Jaxongir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, you can learn about mental preparations before the exam, the preparation process, the agenda, how to improve efficiency, and how to strengthen memory. In addition, there is information about pre-exam mistakes that many people make.